Social frailty is independently associated with geriatric depression among older adults living in northern Japan: A cross‐sectional study of ORANGE registry. Issue 2 (22nd December 2021) - Kume, Yu; Kodama, Ayuto; Takahashi, Tomoko; Lee, Sangyoon; Makizako, Hyuma; Ono, Tsuyosi; Shimada, Hiroyuki; Ota, Hidetaka
Abstract : Aim: To clarify prevalence of social frailty among older adults living in a rural Japanese community, and factors associated with social frailty status. Methods: In total, 322 adults aged ≥65 years living in a Japanese rural community took part in the study from 2018 to 2020. Social frailty was defined as deficiencies of: (i) living alone; (ii) talking with someone every day; (iii) feeling helpful to friends or family; (iv) going out less frequently compared with last year; and (v) visiting friends sometimes. Social frail status was categorized as robust (0), social prefrail (1), and social frail (≥2), according to the summated score of Makizako's criteria. Multiple logistic regression analysis was applied to clarify factors associated with social frailty status. Results: Final samples were classified into 68 persons with social frailty, 98 persons with social prefrailty and 147 persons as robust. We observed the prevalence of social frailty (21.7%) and social prefrailty (31.3%) and the GDS‐15 had significantly high scores in the social frail groups. Social frailty was significantly associated with the GDS‐15 score (odds ratio, 1.33; 95% CI, 1.19–1.49) and TMT‐A (odds ratio, 1.04; 95% CI, 1.01–1.08) and GDS‐15 (odds ratio, 1.13; 95% CI, 1.03–1.26) were extracted as independent variables of social prefrail status, with adjustment for demographics, polypharmacy and lifestyle‐related diseases. Conclusions: Our results suggest that social frailty tends to be increasing gradually in a Japanese rural area, and social prefrailty might be potentially associated with attentional function, as well as the GDS‐15 score. Geriatr Gerontol Int 2022; 22: 145–151 .